Systemic antibiotics and debridement of peri-implant mucositis. A randomized clinical trial - Hallström, Hadar; Persson, G. Rutger; Lindgren, Susann; Olofsson, Maria; Renvert, Stefan (Journal of clinical periodontology, 2012)
Background This RCT compared non‐surgical treatment of peri‐implant mucositis with or without systemic antibiotics. Materials and Methods Forty‐eight subjects received non‐surgical debridement with or without systemic Azithromax ® (4 days), and were followed during 6 months. The checkerboard DNA‐DNA hybridization method was used to analyse the microbiological material. Results Five subjects were excluded due to antibiotic medication during follow‐up. At baseline,1 and 3 months no group differences were found. Statistical analysis failed to demonstrate differences in probing pocket depths (PPD) values at 6 months (Mean diff PPD: 0.5 mm, SE: ±0.4 mm, 95% CI: −0.2, 1.3, p = 0.16). Mean% implant bleeding decreased between baseline and month 6 from 82.6% to 27.3% in the test, and from 80.0% to 47.5% in the control group (p < 0.02). Throughout the study, no study group differences in bacterial counts were found. Conclusion No short‐term differences were found between study groups. The clinical improvements observed at 6 months may be attributed to improvements in oral hygiene. The present study does not provide evidence for the use of systemic antibiotics in treatment of peri‐implant mucositis.